2021
DOI: 10.1111/pai.13657
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐activated protein kinase signaling in childhood asthma development and environment‐mediated protection

Abstract: Background While childhood asthma prevalence is rising in Westernized countries, farm children are protected. The mitogen‐activated protein kinase (MAPK) pathway with its negative regulator dual‐specificity phosphatase‐1 (DUSP1) is presumably associated with asthma development. Objectives We aimed to investigate the role of MAPK signaling in childhood asthma and its environment‐mediated protection, including a representative selection of 232 out of 1062 children from two cross‐sectional cohorts and one birth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 44 publications
(68 reference statements)
0
21
0
Order By: Relevance
“…In recent years, many studies confirmed that inhibiting PI3K−Akt signaling pathway and MAPK signaling pathway could effectively inhibit allergic airway inflammation, ASMC proliferation and migration, and phenotypic switching, so as to alleviate airway remodeling and airway hyperresponsiveness (AHR) in asthma [ 39 42 ]. Additionally, upregulation of dual-specificity phosphatase-1 (DUSP1), a negative regulator in the MAPK signaling pathway, to healthy levels and downregulation of inflammatory MAPKs at the gene and protein levels could reduce the prevalence of childhood asthma [ 43 ]. Proteoglycans enhanced deposition in the airway walls of asthmatics playing a role in airway remodeling, and the difference of deposition in the airway smooth muscle layer of moderate and severe asthmatic patients might affect the functional behavior of airway smooth muscle [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies confirmed that inhibiting PI3K−Akt signaling pathway and MAPK signaling pathway could effectively inhibit allergic airway inflammation, ASMC proliferation and migration, and phenotypic switching, so as to alleviate airway remodeling and airway hyperresponsiveness (AHR) in asthma [ 39 42 ]. Additionally, upregulation of dual-specificity phosphatase-1 (DUSP1), a negative regulator in the MAPK signaling pathway, to healthy levels and downregulation of inflammatory MAPKs at the gene and protein levels could reduce the prevalence of childhood asthma [ 43 ]. Proteoglycans enhanced deposition in the airway walls of asthmatics playing a role in airway remodeling, and the difference of deposition in the airway smooth muscle layer of moderate and severe asthmatic patients might affect the functional behavior of airway smooth muscle [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…That’s to say, p38 MAPK is vital for allergen induced epithelial production of IL-25 and thymic stromal lymphopoietin (TSLP), further mediating the type-2 allergic response in asthma ( Yu et al, 2010 ; Lin et al, 2015 ; Southworth et al, 2018 ). Previous studies have confirmed that dual-specificity phosphatase1 (DUSP1) also plays vital role in anti-inflammation by deactivating MAPKs through dephosphorylation ( Pulido and Lang, 2019 ; Xin et al, 2021 ; Theodorou et al, 2022 ; Xing and Wong, 2022 ). Besides, Studies have confirmed that JNK is essential for airway inflammation via modulating RAGE/β-catenin signaling ( Huang et al, 2021a ).…”
Section: Asthma-associated Pathogenesismentioning
confidence: 97%
“…Molecular studies have indicated that Mitogen-activated protein kinase (MAPK) pathways, including extracellular signal-regulated kinase 1/2 (ERK1/2), p38 mitogen-activated protein kinase and c-Jun NH2-terminal kinase (JNK), are involved in the inflammatory response and development of airway remodeling during childhood asthma ( Lee et al, 2019b ; Jia et al, 2019 ). Concretely, ERK1/2 is involved in airway remodeling ( Defnet et al, 2019 ), while p38 MAPK and JNK are considered as anti-inflammation targets to regulate inflammatory processes via phosphorylation of downstream mediators in childhood asthma ( Kim and Choi, 2010 ; Pulido and Lang, 2019 ; Theodorou et al, 2022 ). However, literatures about the pathogenesis of MAPK pathways in childhood asthma are limited.…”
Section: Asthma-associated Pathogenesismentioning
confidence: 99%
“…Baek et al have documented that exposure to phthalates are associated with airway dysfunction in childhood and this effect was partially attributable to increased serum periostin levels (6). Regarding the association between the genes and environment, Theodorou et al (7) have investigated the role of mitogen-activated protein kinase (MAPK) pathway in 232 children who were selected from two cross-sectional cohorts and one birth cohort study. They have isolated peripheral blood mononuclear cells (PBMC) from children with asthma along with healthy controls and stimulated them with farm-dust extracts or lipopolysaccharide.…”
mentioning
confidence: 99%